Study of general constitutional rights and responsibilities of citizens in Ukraine at the present stage of development of law - Білоскурська, Олена Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with the further development of theoretical problems of the constitutional obligations of a manand a citizen in Ukraine. The author’s definition of the constitutional obligations of a man and a citizen in Ukrainehas been made; their essence, content and form have been elucidated.